A flexible hybridized electromagnetic-triboelectric nanogenerator and its application for 3D trajectory sensing. (August 2020) - Wan, Ji; Wang, Haobin; Miao, Liming; Chen, Xuexian; Song, Yu; Guo, Hang; Xu, Chen; Ren, Zhongyang; Zhang, Haixia
Abstract: Here, we report a flexible hybridized electromagnetic-triboelectric nanogenerator composed of Polydimethylsiloxane (PDMS), multi-walled carbon nanotube (MWCNT) and NdFeB microparticles. The magnetic and conductive Polydimethylsiloxane (MC-PDMS) is soft and flexible enough so that it can be attached onto unsmooth cloth and human skin by adhesive tape and even sewn on the fabric. It works not only as the flexible magnetic polymer of the EMG, providing electromagnetic induction in the copper coil, but also used as TENG′s electrode, conducting tribo-electricity. Therefore as a TENG, it generates peak to peak of open-circuit voltage and short-circuit current at 103 V and 7.6 μA respectively, and a maximum power density of 7.3 μW/cm ∧ 2 at 18.8 MΩ. At the same time, as an EMG, the corresponding peak to peak voltage, current and maximum power are 1.37 V, 1.03 mA and 0.04 mW/cm ∧ 2 at 1 KΩ, respectively. It can charge a capacitance of 10 μF to 3 V in 110 s that is superior to the TENG only and EMG only. Furthermore, it can be utilized for self-powered 3D trajectory sensing which involves the capacity of height information detecting above the coil array. This device shows a great potential for applications in wearable electronics and human-machine fields. Graphical abstract: A flexible hybridized electromagnetic-triboelectric nanogenerator composed of Polydimethylsiloxane (PDMS), multi-walled carbon nanotube (MWCNT) and NdFeB microparticles was reported. It was magnetized by a pulsed magnetizer, after which it can be utilized for hybridized energy harvesting from human motions as well as self-powered 3D trajectory sensing. The device shows a great potential for applications in wearable electronics and human-machine fields. Image 1 Highlights: It shows a great potential for applications in wearable electronics and human-machine fields. The magnetic and conductive MC-PDMS is soft and flexible enough so that it can be utilized as a wearable device. The device can be utilized for hybridized energy harvesting from human motions and a self-powered 3D trajectory sensing. It shows a great potential for applications in wearable electronics and human-machine fields.